Meta-analysis of voxel-based morphometry studies of gray matter abnormalities in patients with mesial temporal lobe epilepsy and unilateral hippocampal sclerosis. - Zheng, Liyun; Bin, Guo; Zeng, Hongwu; Zou, Dongfang; Gao, Junling; Zhang, Jian; Huang, Bingsheng (Brain Imaging & Behavior, 2018)
We aimed to perform a meta-analysis to systematically determine the most consistent regions of gray matter volume (GMV) abnormality in patients of unilateral mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS), and to reveal the difference of GMV abnormality between the patients with left-sided and right-sided MTLE-HS. A comprehensive and systematic search was performed in PubMed for voxel-based morphometry (VBM) studies of MTLE-HS. A total of 12 MTLE-HS studies, including 9 left-sided MTLE-HS (LMTLE-HS) and 8 right-sided MTLE-HS (RMTLE-HS) studies were included. The activation likelihood estimation (ALE) method was applied in our meta-analysis. Compared to the healthy controls, MTLE-HS patients showed significant GMV decrease in the parahippocampal gyrus, left pulvinar and right pyramis. For LMTLE-HS, the most consistent GMV decrease was detected in the left parahippocampal gyrus. For RMTLE-HS, the most consistent GMV decrease was found in the right parahippocampal gyrus. No shared regions of significant GMV reduction were found between LMTLE-HS and RMTLE-HS either. This meta-analysis revealed that MTLE-HS patients had significant GMV reduction even beyond the hippocampus, and the subtypes showed distinct reduction patterns. Our findings, if were further verified with larger samples, would have implications for the clinical diagnosis of MTLE-HS.